Battery, electrochemical device and electric device

By adding silicon to the negative electrode active material layer of the battery and optimizing the structural parameters of the electrode ear and the negative electrode sheet, the problem of poor fast charging performance of the battery is solved, and more efficient charging performance and energy density are achieved.

CN119601750AActive Publication Date: 2025-03-11CALB (JIANGMEN) CO LTD +1

Patent Information

Application Number
CN202411807291.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-10
Publication Date
2025-03-11
Estimated Expiration
2044-12-10

AI Technical Summary

Technical Problem

The existing batteries have shortcomings in fast charging performance, resulting in low battery charging efficiency.

Method used

By adding an appropriate amount of silicon to the negative electrode active material layer of the battery, the connection width between the electrode and the negative electrode sheet and the maximum distance between the electrode and the negative electrode sheet are controlled to satisfy the specific parameter relationship to improve the fast charging performance of the battery.

Benefits of technology

While ensuring the energy density of the battery, it can effectively improve the pole chip overcurrent capability, improve the battery's fast charging performance, and shorten the charging time.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119601750A_ABST
    Figure CN119601750A_ABST
Patent Text Reader

Abstract

The invention discloses a battery, an electrochemical device and a power utilization device.The battery comprises a battery cell, and the battery cell comprises a pole piece and a pole lug arranged on the pole piece; the lithium ion battery is characterized in that the negative electrode active material layer of the pole piece contains silicon, the percentage content of the silicon in the negative electrode active material layer is b, and the unit is%; the longest distance between the tab and the end part of the pole piece in the length direction is d, the width of the connecting position of the tab and the pole piece is m, and the units of d and m are the same; b, d and m meet the following relation: # imgabs0 #. By comprehensively controlling the value of # imgabs1 #, not only can the battery with relatively high energy density be obtained, but also the battery can be ensured to have relatively good battery fast charging performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the field of batteries, and in particular to a battery, an electrochemical device and an electrical device. Background Art

[0002] The battery cell includes a tab, which can be divided into a top tab or a side tab according to the location. The side tab is the tab extending from the short side of the pole piece along the direction of the long side of the pole piece, and the top tab is the tab extending from the long side of the pole piece along the direction of the short side of the pole piece. Conventional batteries usually have the tab set on the short side or one side close to the short side, and then are made by lamination or winding.

[0003] The tabs are used to transfer the current in the battery cell to the external circuit. Currently, in order to increase the energy density of the battery, the length of the battery tabs is usually made longer and longer, resulting in uneven current density distribution along the length direction of the tabs. In particular, the current density is relatively small on the tabs far away from the tabs, which increases the impedance of the tabs, which is not conducive to improving the fast charging performance of the battery. Summary of the invention

[0004] Therefore, the technical problem to be solved by the present invention is that the battery in the prior art has the defect of poor fast charging performance, and thus a battery, an electrochemical device and an electrical device are provided to improve the above problem.

[0005] To achieve the above object, the present invention provides a battery, comprising a battery cell, wherein the battery cell comprises a negative electrode sheet and a tab arranged on the negative electrode sheet; the negative electrode sheet contains silicon in the negative electrode active material layer, and the mass percentage of silicon in the negative electrode active material layer is b, in %; parallel to the long side direction of the negative electrode sheet, the longest distance between the tab and the end of the negative electrode sheet is d, in mm; the leading direction of the tab is a first direction, and perpendicular to the first direction, the dimension of the connection between the tab and the negative electrode sheet is the width m of the tab, in mm; b, d and m satisfy the following relationship:

[0006]

[0007] The present invention provides an electrochemical device comprising the battery.

[0008] The present invention provides an electrical device, comprising the electrochemical device mentioned above.

[0009] The beneficial effects of the present invention are:

[0010] A battery disclosed in the present invention comprises a battery cell, wherein the mass percentage b of silicon in the negative electrode active material layer, the longest distance d between the tab and the ends of the negative electrode sheet in the long side direction, and the width m of the tab are controlled so that b, d and m satisfy The present invention can effectively and comprehensively improve the electrode current capacity and improve the battery fast charging performance by controlling the above parameters while ensuring the battery energy density. BRIEF DESCRIPTION OF THE DRAWINGS

[0011] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0012] Figure 1 2 is a schematic diagram of a structure in which the tab lead-out direction is ejection in an embodiment of the present invention;

[0013] Figure 2 It is a schematic diagram of the structure in which the tab lead-out direction is lateral in an embodiment of the present invention. DETAILED DESCRIPTION

[0014] The following examples are provided for a better understanding of the present invention, but are not intended to limit the best mode of implementation, nor to limit the content and protection scope of the present invention. Any product identical or similar to the present invention obtained by anyone under the inspiration of the present invention or by combining the features of the present invention with other prior arts shall fall within the protection scope of the present invention.

[0015] If no specific experimental steps or conditions are specified in the examples, the conventional experimental steps or conditions described in the literature in the field can be used. If no manufacturer is specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially.

[0016] The "range" disclosed in the present invention is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of the particular range. The range defined in this way can be inclusive or exclusive of the end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, if a range of 50%-90% and 60%-80% is listed for a particular parameter, it is understood that the range of 50% to 80% and 60% to 90% is also expected. In addition, if the minimum range values ​​1 and 2 are listed, and if the maximum range values ​​3, 4 and 5 are listed, the following ranges can all be expected: 1 to 3, 1 to 4, 1 to 5, 2 to 3, 2 to 4 and 2 to 5. In this application, unless otherwise specified, the numerical range "a to b" represents an abbreviation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0.5-4" means that all real numbers between "1-4" have been listed in this article, for example: 0.5, 1, 1.5, 2, 2.5, 3, 3.5, 4, etc. "0.5-4" is just an abbreviation of these numerical combinations.

[0017] The present invention provides a battery, comprising a battery cell, wherein the battery cell comprises a negative electrode sheet and a pole ear arranged on the negative electrode sheet; the negative electrode active material layer of the negative electrode sheet contains silicon, and the mass percentage of silicon in the negative electrode active material layer is b, in units of %; parallel to the long side direction of the negative electrode sheet, the longest distance between the pole ear and the end of the pole sheet is d, in units of mm; the leading direction of the pole ear is a first direction, and the dimension of the connection between the pole ear and the pole sheet in the direction perpendicular to the first direction is the width m of the pole ear, in units of mm; b, d and m satisfy the following relationship: In the present invention The value can be any number between -3.1 and -0.11, for example: -3.1, -3.0, -2.5, -2, -1.5, -1, -0.5, -0.13, -0.11, etc.

[0018] In the present invention, b is the mass percentage of silicon in the negative electrode active material layer. By adding silicon material to the negative electrode active material layer, the overall energy density of the battery can be improved, but at the same time, the addition of silicon will also affect the impedance of the pole piece. A larger silicon content will increase the impedance of the pole piece, affecting the fast charging performance. d is the distance between the pole ear and the end of the pole piece. The pole ear is used for overcurrent. The distance between the pole ear and the end of the pole piece affects the transmission distance of the current. The position away from the pole ear increases the current transmission impedance, resulting in a low current density at the end of the pole piece away from the pole ear, affecting the fast charging performance of the battery. m is the connection width between the pole ear and the pole piece body. The connection width will affect the current size. The larger the connection width, the greater the current carrying capacity, the less resistance and energy loss caused by resistance, and the greater the current.

[0019] The present invention improves the problem of increased electrode impedance caused by the long electron transmission path while taking into account the battery energy density by comprehensively controlling the relationship between the silicon content b, the distance d between the electrode tab and the end of the negative electrode sheet, and the connection width m between the electrode tab and the electrode body. Specifically, when the b content is too low, the energy density is low; when the b and d contents are too high, the electrode impedance will be large; when the m value is too small, the current carrying capacity will be poor; therefore, if the m / (d×b) value is too small, the electron transmission path will be too long, the electrode end impedance will be large, and the DCR will be large, resulting in poor fast charging performance; if the m / (d×b) value is too large, its DCR is small, the fast charging performance is good, but the battery energy density is low; after research, it was found that the relationship between the m / (d×b) value and the fast charging performance and energy density is not linear, and it is impossible to simply use the m / (d×b) value to screen out batteries with good fast charging performance and energy density; the present invention uses the lg function to process the m / (d×b) value, and the processed value can realize reasonable data analysis and application, and the processed data can effectively obtain batteries with good fast charging performance and energy density. That is, by controlling The value is between -3.1 and -0.11, which can achieve the purpose of improving the fast charging performance of the battery while meeting the energy density requirements.

[0020] Further, by The value is controlled within a more preferred range of -1.8 to -0.7, and the comprehensive performance of the energy density and the fast charging performance of the battery of the present invention is better.

[0021] In one of the preferred embodiments, the present invention optimizes the percentage b of silicon in the negative electrode active material layer, unit: %; specifically, the b value cannot be too small, otherwise it will affect the battery energy density; the b value cannot be too large, otherwise the b value will be too large and the silicon content will be too high, which will easily cause the electrode to have a greater impedance, thereby affecting the fast charging performance of the electrode. Among them, the reasons why the excessive silicon content causes the electrode to have a greater impedance are: 1) The conductivity of silicon itself is poor. Compared with carbon materials, the conductivity of pure silicon is much lower. When the silicon content increases, the overall conductivity of the composite material decreases, resulting in an increase in internal resistance, which in turn affects the fast charging performance; 2) The volume change of silicon is large. Silicon will undergo significant volume expansion and contraction during the charging and discharging process, up to about 300%. This large volume change will lead to poor contact between material particles, or even breakage, forming "dead silicon", which will block the electron transmission path and increase the resistance of the electrochemical reaction, thereby increasing the internal resistance of the battery; 3) In the first charge and discharge cycle, a layer of solid electrolyte interface (SEI) film will form on the silicon surface. Due to the large volume change of silicon, the SEI film will continuously break and re-form during the charging and discharging process, which not only consumes lithium ions in the electrolyte, but also increases the interface impedance, further increasing the internal resistance of the battery; 4) As the silicon content increases, the structural stability of the composite material deteriorates, and it is prone to powdering and falling off, reducing the effective contact area and increasing the contact resistance of the battery. Therefore, the b value in the present invention ranges from 1.25 to 16, preferably from 2.5 to 7.5. For example, the b% is controlled to be 1.25%, 1.5%, 2%, 3%, 5%, 7%, 9%, 11%, 13%, 15%, etc.

[0022] In one preferred embodiment, the present invention optimizes the longest distance d between the pole tab and the ends at both ends of the long side extension direction of the negative electrode sheet. When the pole tab extends from the long side extension direction of the negative electrode sheet, the longest distance from the pole tab to the end of the pole sheet is the pole sheet length; when the pole tab is led out perpendicular to the long side extension direction of the pole sheet, the longest distance from the pole tab to the end of the pole sheet is the distance between the pole tab and the end of the pole sheet disposed away from the pole tab. In the present invention, the d value cannot be too large. If the d value is too large, the electron transmission path will be too long, resulting in uneven current density distribution and large electrode impedance, which will affect the fast charging performance; therefore, in electrodes of the same length, the smaller the d value, the better; but in electrodes of different lengths, the d value cannot be too small. If it is too small, it is usually necessary to shorten the electrode length, which will affect the energy density of the battery; therefore, the d value in the present invention is preferably 42 to 1000, preferably 250 to 450, and the unit is mm; for example: the d value is controlled to be 42, 45, 50, 60, 80, 100, 150, 200, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 960, 1000, etc.

[0023] In one preferred embodiment, the lead-out direction of the pole ear is the first direction, and the dimension of the connection between the pole ear and the negative electrode sheet in the perpendicular direction is the width m of the pole ear. The present invention optimizes the width m of the connection position between the pole ear and the negative electrode sheet; the m value cannot be too small. If the m value is too small, the flow cross section is small, the current carrying capacity is small, the flow capacity of the pole sheet is poor, and the internal resistance increases. In addition, the m value cannot be too high. When the m value is too high, it may cause problems such as increased impedance, low energy density, and increased packaging difficulty. The reason is that the space of the battery is limited, and an overly large pole ear may cause the battery to be unable to adapt to these spaces, affecting the integration of the battery and increasing the difficulty of battery packaging; and the increase of the pole ear will increase the overall weight of the battery, thereby reducing the energy density (WH / KG). Therefore, the m value in the present invention is 9-960, preferably 50-180; for example: the m value is controlled to be 9, 10, 15, 20, 25, 30, 35, 40, 45, 50, 60, 80, 100, 150, 200, 350, 400, 450, 500, 550, 600, 650, 700, 750, 800, 850, 900, 950, 960, etc.

[0024] The present invention further optimizes the surface density of the negative electrode active material layer. The surface density will also affect the fast charging performance of the battery. When the surface density is small, the electrode sheet is thin, the battery impedance is small, and the lithium ion transmission distance is short, which is conducive to improving the fast charging performance. However, the surface density cannot be too small. If the surface density is too small, the amount of coated active material is small, and the battery energy density is low; the surface density cannot be too large. If it is too large, the lithium ion transmission path is large, the battery internal resistance is large, and congestion is easy to occur on the lithium ion migration path, causing the lithium ions to be unable to be completely deintercalated in a short time, and the polarization increases, which leads to low charging efficiency of the battery during conventional charging or fast charging, which is not conducive to improving the fast charging capability; the surface density in the present invention is preferably 90-300g / m 2 ; For example: control the surface density to 90g / m 2 , 100g / m 2 , 150g / m 2 , 200g / m 2 , 250g / m 2 , 300g / m 2 wait.

[0025] The present invention further optimizes the compaction density of the negative electrode active material layer. If the compaction density is too large, the distance between particles will decrease, the contact will be closer, and the electronic conductivity will be enhanced, but the ion movement channel will be reduced or blocked, which is not conducive to the rapid movement of a large number of ions. The migration speed of lithium ions cannot keep up with the charging speed, resulting in large internal polarization of the battery. The battery can easily reach the upper voltage limit during fast charging, so it is easy to jump to a lower charging rate during fast charging, so that the charging rate to achieve the required SOC is low, resulting in poor fast charging ability and longer fast charging time; if the compaction density is too small, the distance between particles will increase, the ion channels will increase, and the liquid absorption of the electrolyte will increase, which is conducive to the rapid movement of ions. However, due to the large distance between particles, too many gaps will cause the migration path of lithium ions in the electrode to become longer. This will increase the diffusion time and difficulty of lithium ions in the electrode. During fast charging, lithium ions need to quickly migrate from the electrolyte to the inside of the electrode material for embedding. If the migration path of lithium ions is too long, the charging speed will slow down, affecting the fast charging efficiency; therefore, the compaction density is comprehensively controlled to be 1.2 to 2.3 g / m 3 When the compaction density is relatively low, for example, the compaction density is 1.2 to 1.6 g / m 3 When The value of is in the range of -1.8 to -0.7, which can make the battery have better fast charging performance; when the compaction density is relatively high, for example, the compaction density is 1.6 to 2.3 g / m 3 When the formula m is controlled to be in the range of 50 to 960, the battery can have a better fast charging performance. The compaction density can be 1.2 g / m 3 , 1.4g / m 3 , 1.5g / m 3 , 1.6g / m 3 , 1.7g / m 3 , 1.8g / m 3 , 1.9g / m 3 , 2.0g / m 3 , 2.3g / m 3 wait.

[0026] As a preferred setting, the pole ear is a side-out pole ear, that is, the pole ear is extended from the long side of the negative electrode sheet, perpendicular to the direction of the pole ear extension, and the ratio of the pole ear width to the width of the negative electrode sheet is greater than or equal to 0.5 and less than or equal to 1. This setting can better increase the current carrying capacity, thereby reducing the internal resistance and improving the fast charging performance of the battery cell.

[0027] As a preferred arrangement, in order to ensure a higher energy density, the long side length of the negative electrode sheet is ≥300 mm; the long side length of the negative electrode sheet can be 300-1100 mm; specifically, it can be 300 mm, 400 mm, 500 mm, 600 mm, 700 mm, 800 mm, 900 mm, 1000 mm, 1100 mm.

[0028] And / or, the battery cell is a laminated battery cell, which refers to a battery cell in which a positive electrode sheet, a negative electrode sheet, and a separator are formed by a lamination process.

[0029] The following discloses an embodiment of an electrochemical device and an electrical device of the present invention as appropriate. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there may be cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present application and is not intended to limit the subject matter described in the claims.

[0030] [Electrochemical device]

[0031] The electrochemical device in the present invention is a secondary battery, also known as a rechargeable battery or storage battery, which refers to a battery that can be recharged to activate the active material after the battery is discharged and continue to be used.

[0032] Normally, a secondary battery includes a battery cell, an electrolyte and an outer packaging shell. The battery cell includes a pole piece consisting of a positive electrode sheet and a negative electrode sheet, a pole ear arranged on the pole piece and a diaphragm arranged between the positive electrode sheet and the negative electrode sheet. The pole ear is usually an integrally formed structure with the current collector on the pole piece. The battery cell and the electrolyte are assembled in the outer packaging shell. During the battery charging and discharging process, active ions (such as lithium ions) are embedded and removed back and forth between the positive electrode sheet and the negative electrode sheet. The diaphragm is arranged between the positive electrode sheet and the negative electrode sheet, mainly to prevent the positive and negative electrodes from short-circuiting, and at the same time to allow active ions to pass through. The electrolyte is between the positive electrode sheet and the negative electrode sheet, mainly to conduct active ions.

[0033] As an example, the preparation process of a secondary battery is as follows: prepare the positive electrode sheet and the negative electrode sheet separately; the pole ear is formed during the pole sheet forming process. Specifically, during the pole sheet processing process, the slurry is first coated on the current collector, and a coating area and a blank area will be formed on the current collector; after drying, the slurry is rolled and then cut to cut out the pole ear in the blank area; the material of the pole ear is the same as the material of the current collector in the pole sheet. For example, when the material of the current collector in the negative electrode sheet is copper, the material of the pole ear on the negative electrode sheet is also copper. The pole sheet with the pole ear and the diaphragm are stacked in order so that the diaphragm is between the positive and negative electrode sheets to play a role of isolation, and then wound and placed in the outer packaging shell. After drying, the electrolyte is injected, and the secondary battery is obtained through vacuum packaging, standing, forming, shaping and other processes.

[0034] [Positive electrode]

[0035] The positive electrode sheet generally includes a positive electrode current collector and a positive electrode film layer disposed on at least one side of the positive electrode current collector. The positive electrode film layer includes a positive electrode active material, which can be any positive electrode active material disclosed in the prior art or a positive electrode active material optimized on the prior art basis.

[0036] The present invention does not particularly limit the type of positive electrode active material of the positive electrode sheet. As an example, the positive electrode active material in the present invention includes lithium-containing transition metal oxides (e.g., LiCoO2), phosphides (e.g., LiFePO4) or lithium-inserted compounds (e.g., lithium cobalt oxide, lithium nickel oxide and other positive electrode materials for binary lithium batteries, or lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide and other positive electrode materials for ternary lithium batteries). As one of the configurations, the positive electrode active material in the present invention is preferably LiNi x Co y Mn z O2 material, wherein 1>x≥0.5, x+y+z=1.

[0037] In some embodiments, the positive electrode sheet can be prepared in the following manner: the components for preparing the positive electrode sheet, such as the positive electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (for example, N-methylpyrrolidone) to form a positive electrode slurry; the positive electrode slurry is coated on the positive electrode collector, and after drying, rolling, cutting and other processes, the positive electrode sheet can be obtained.

[0038] In the present invention, the binder is used to improve the adhesion between the positive electrode active material particles and the adhesion between the positive electrode active material and the current collector. The present invention does not particularly limit the type of binder for the positive electrode sheet, and the binder in the present invention can be a conventional choice in the battery field. Specifically, the binder can be at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyvinyl alcohol (PVA), styrene-butadiene rubber (SBR), polyacrylonitrile (PAN), polyimide (PI), polyacrylic acid (PAA), polyacrylate, polyolefin, sodium carboxymethyl cellulose (CMC) or sodium alginate.

[0039] The present invention has no particular limitation on the positive electrode current collector as long as it has conductivity and does not cause adverse chemical changes in the battery, and can use, for example: stainless steel, aluminum, nickel, titanium, fired carbon; or aluminum or stainless steel surface-treated with one of carbon, nickel, titanium, silver, etc.

[0040] [Negative electrode]

[0041] The negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer disposed on at least one side of the negative electrode current collector, wherein the negative electrode active material layer contains silicon, that is, the negative electrode active material included in the negative electrode active material layer includes at least a silicon-based material, and the present invention has no specific restrictions on the type of silicon-based material. As an example, the silicon-based material may be one or more of a silicon-oxygen material and a silicon-carbon material. In some embodiments, the negative electrode active material in the negative electrode active material layer may also optionally include one or more of artificial graphite, natural graphite, and hard carbon.

[0042] In some embodiments, the negative electrode sheet can be prepared in the following manner: the components for preparing the negative electrode sheet, such as the negative electrode active material, the conductive agent, the binder and any other components are dispersed in a solvent (such as water) to form a negative electrode slurry; the negative electrode slurry is coated on the negative electrode collector, and after drying, rolling, cutting and other processes, a negative electrode sheet with a tab can be obtained.

[0043] The present invention has no specific limitation on the type of negative electrode conductive agent. In some embodiments, as an example, the negative electrode conductive agent can be one or more conventional negative electrode conductive agents such as acetylene black and carbon nanotubes;

[0044] The present invention has no specific limitation on the type of negative electrode binder. In some embodiments, as an example, the binder may be one or more conventional negative electrode binders such as styrene-butadiene rubber latex (SBR), polyvinylidene fluoride (PVDF), etc.;

[0045] The present invention has no specific limitation on the type of the negative electrode current collector. In some embodiments, as an example, the negative electrode current collector may be one of conventional negative electrode current collectors such as copper foil.

[0046] [Electrolyte]

[0047] The electrolyte plays the role of conducting ions between the positive electrode and the negative electrode. The present invention has no specific restrictions on the type of electrolyte, which can be selected according to needs. As an example, the electrolyte of the present invention can be various electrolytes suitable for electrochemical energy storage devices in the art. The electrolyte includes an electrolyte and a solvent, and the electrolyte can generally include a lithium salt, and additives can also be added to the electrolyte.

[0048] Specifically, the lithium salt includes at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bis(fluorosulfonyl)imide (LiFSI), lithium bis(trifluoromethanesulfonyl)imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobis(oxalatophosphate) (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP). The concentration of the electrolyte in the electrolyte may be 0.5 to 5 mol / L.

[0049] Specifically, the solvent includes at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).

[0050] In some embodiments, as examples, the additive may be conventional electrolyte additives such as fluoroethylene carbonate (FEC), chloroethylene carbonate (CEC), and vinylene carbonate (VC).

[0051] [Diaphragm]

[0052] In some embodiments, the secondary battery further includes a separator. The present application has no particular limitation on the type of separator, and any known porous structure separator with good chemical stability and mechanical stability can be selected.

[0053] In some embodiments, as an example, the separator is one of PP, PE, and PP / PF, and the surface of the separator may be provided with an inorganic coating and / or an organic coating. The inorganic coating may be selected from alumina ceramic layer, beryl, etc.; the organic coating may be selected from PVDF, etc.

[0054] Example

[0055] An electrochemical device, such as a secondary battery, comprises a positive electrode sheet, a negative electrode sheet with a tab, a separator, an electrolyte and an outer packaging shell.

[0056] 1. Preparation of positive electrode

[0057] The specific preparation process of the positive electrode sheet is as follows: obtain the positive electrode active material LiNi 0.9 Co 0.05 Mn 0.05 O2, the positive electrode active material, the conductive agent acetylene black, and the binder PVDF are mixed in a mass ratio of 92:4:4, the solvent NMP is added, and the system is stirred under the action of a vacuum mixer until the system is uniform to obtain a positive electrode slurry; the positive electrode slurry is coated on both surfaces of the aluminum foil, and after drying at room temperature, it is transferred to an oven for further drying, and then cold pressed and cut to obtain a positive electrode sheet.

[0058] 2. Preparation of negative electrode sheet

[0059] The specific preparation process is as follows: a negative electrode active material silicon carbon and graphite are mixed in a mass ratio as shown in Table 1; the mixture, conductive agent SWCNT, conductive agent SP, thickener CMC, binder SBR, and binder PAA are mixed in a mass ratio of 96:0.05:0.95:0.2:1.5:1.3; deionized water is added and stirred under the action of a vacuum mixer until the system is uniform to obtain a negative electrode slurry; the negative electrode slurry is coated on both surfaces of a copper foil, dried at room temperature, transferred to an oven for further drying, and then cold pressed and cut to obtain a negative electrode sheet with a tab; there are two ways to set the tab in the lead-out direction, one is as follows Figure 1 The ejection shown is as follows. Figure 2 The side is shown; in the present invention, the width of the negative electrode sheet is 200 mm, and the parameters of the lead-out direction of the tab, the compaction density of the negative electrode sheet, the surface density of the negative electrode sheet, the length L of the negative electrode sheet after cutting, the longest distance d between the tab and the end of the negative electrode sheet, and the width of the tab are shown in Table 1.

[0060] The above-mentioned negative electrode active material silicon carbon is silicon carbon prepared by CVD deposition method. The preparation process of the silicon carbon is as follows: through the adsorption force of porous carbon, at different temperatures, silane (~450°C, silane decomposes to produce silicon element) is gradually infiltrated into the carbon skeleton; acetylene carbon coating (~550°C) forms a stable coated carbon layer / a-Si@a-PC structure on the surface of silicon carbon; the present invention can control the number of deposited silicon grains in the porous carbon by controlling parameters such as silane flow rate and deposition time, thereby adjusting the percentage of silicon in the negative electrode active material layer.

[0061] 3. Obtaining the diaphragm

[0062] The diaphragm in this embodiment is a diaphragm with a coating on a base film, the base film is selected from polyethylene (PE), and the coating is an aluminum oxide ceramic layer.

[0063] 4. Preparation of electrolyte

[0064] The preparation process is as follows: in a glove box filled with argon, fluoroethylene carbonate (FEC), ethyl methyl carbonate (EMC), dimethyl carbonate (DMC), and propylene carbonate (PC) are mixed in a mass ratio of 15:20:60:5 to obtain an organic solvent, and then the fully dried lithium salt LiPF6 is dissolved in the mixed organic solvent, followed by adding 0.5% 1,3-propane sultone, 0.5% tris(trimethylsilyl) phosphate, and 1% vinyl sulfate to the electrolyte, and stirring until completely dissolved to form an electrolyte with a lithium salt concentration of 1.3M.

[0065] 5. Assembly of secondary batteries

[0066] The specific process is: stack the above-mentioned positive electrode sheet, separator, and negative electrode sheet in order, so that the separator is placed between the positive and negative electrode sheets to play an isolating role, and then obtain the electrode assembly through the stacking process; place the electrode assembly in an outer packaging shell, inject electrolyte after drying, and obtain a lithium-ion secondary battery through conventional vacuum packaging, standing, formation, shaping and other processes.

[0067] Table 1

[0068]

[0069]

[0070] In the above Table 1, the test methods of the parameters b, surface density and compacted density are as follows:

[0071] 1. Test of the percentage content b of silicon in the negative electrode active material layer:

[0072] The alkaline dissolution-ICP method is used to test the silicon content in the negative electrode sheet. Specifically, the battery is discharged at 0.33C, cleaned with solvent DMC, soaked for 48 hours, and dried at 60℃ to scrape the powder of the negative electrode active material layer; weigh the powder sample, place it in a nickel crucible pre-filled with potassium hydroxide, add a little potassium hydroxide to cover the surface of the sample, drip two drops of ethanol, place it on an electric furnace and heat it until the potassium hydroxide melts and dehydrates, then move it to a muffle furnace at 1100℃, keep it molten and keep it warm for 8 hours, take out the nickel crucible, and cool it slightly. Put it in a 300mL plastic beaker, add hot water for extraction, and wash out the crucible after the reaction. Add HCl to the extract to acidify it, and add hydrogen peroxide and hydrochloric acid to form a mixed acid to make the silicon-containing compound more thoroughly converted to silicon ions; after cooling, wash it out with water, transfer it to a 100mL volumetric flask, dilute to volume, and shake it well. After standing, take the solution into another 100mL volumetric flask, dilute to volume, shake it well, stand and clarify, and obtain the solution to be tested. At the same time, prepare a blank solution as a control. No sample is added to the blank solution. Make a blank sample control according to the operating procedures to eliminate possible influences during the operation.

[0073] Perform ICP test on the solution to be tested, select the element detection spectrum wavelength, and set the experimental conditions: According to the characteristics of the sample and the solution to be tested, perform ICP test on the Si element detection spectrum wavelength of 288.158nm, and test the Si content of the element through ICP test.

[0074] 2. Measurement of the longest distance d between the pole ear and the end of the pole piece in the length direction and the width m of the connection between the pole ear and the pole piece:

[0075] The longest distance d between the pole ear and the end of the pole piece in the length direction is as follows Figure 1 As shown, where L is the pole piece length.

[0076] 3. Measurement of the surface density and compaction density of the negative electrode active material layer;

[0077] The battery to be tested is charged to 0% SOC state, and the battery is disassembled in a closed environment at a temperature of about 25°C. The negative electrode sheet is obtained after disassembly, and the negative electrode sheet is soaked in DMC for 48 hours. The DMC is replaced every 24 hours. The cleaned negative electrode sheet is placed in an oven at 70°C and baked for 2 hours to remove the residual DMC solvent to obtain the electrode sheet to be tested.

[0078] Use a sampler to sample the electrode to be tested, and obtain a disc punched into a fixed area, the area of ​​which is recorded as S0. In order to ensure the accuracy of the test, select a disc from the middle of the electrode, and take three or more discs as parallel samples. Use an electronic balance to weigh the weight m1 of the discs respectively, and use a micrometer to measure the thickness h1 of the discs. In the process of measuring the thickness of the negative electrode with a micrometer, it is necessary to gradually move the micrometer screw close to the small anvil and clamp the electrode in it. After each point is measured, clean the graphite powder on the cross section and repeat the zeroing; finally, add appropriate amount of deionized water to each of the three discs, gently wipe off the coating on the disc with dust-free paper to expose the copper foil, and let it stand (dry) at room temperature for 10 minutes. After the copper foil is dry, weigh the mass of the three copper foils respectively and record it as m0, and use a micrometer to measure the thickness h0 of the disc.

[0079] The thickness measurement process requires testing the thickness of the wafer at five points in the longitudinal direction. Three wafers need to be tested for each battery, and then the average value of all test results is taken.

[0080] Surface density measurement: Calculate the surface density A obtained by the sampler by (m1-m0) / S0. The value A is the surface density of the negative electrode active material layer. When the units of m1 and m0 are mg and the unit of S0 is cm 2 When A is in mg / cm 2 , converted to g / m 2 When , the A value needs to be *0.1.

[0081] Measurement of compaction density: The coating thickness is obtained according to h2=h1-h0, and the compaction density of the negative electrode active material layer is obtained according to A / h2.

[0082] The performance test of the batteries of the embodiment and the comparative example under the above parameter conditions is carried out, and the test method is as follows:

[0083] 1. Trial production of three electrodes and lithium plating.

[0084] Prepare several enameled copper wires with a diameter of 40um, soak them in 98% concentrated sulfuric acid for 3 hours, then rinse them with anhydrous ethanol for 5 minutes, soak them in 20% dilute hydrochloric acid for 20 minutes, then rinse them with deionized water for 5 minutes, and finally place the treated copper wires in a 50℃ drying oven until the surface of the copper wires is dry. The treated copper wires will be used as the reference electrode of the battery.

[0085] The positive electrode, the separator, the reference electrode, the separator, and the negative electrode are assembled in this order, and the tab of the reference electrode is led out from the top of the battery.

[0086] The reference electrode was plated with lithium using a blue button cell charging and discharging device as follows: (1) forward lithium plating: the electrode connection method was positive electrode + reference electrode, the current was 0.1 mA, and the time was 5 h; (2) reverse lithium plating: the electrode connection method was negative electrode + reference electrode, the current was 0.1 mA, and the time was 5 h.

[0087] 2. Fast charging performance test.

[0088] The test method is as follows:

[0089] a. Charge the battery at a constant current of 0.33C to an upper voltage of 4.25V, then charge at a constant voltage until the cut-off current is less than or equal to 0.05C, and then discharge;

[0090] Repeat the above steps 3 times, and take the discharge capacity of the third time as the discharge capacity of the battery;

[0091] b: Based on the battery capacity in a, the battery is charged at 0.33C to 10% SOC; recorded as T0;

[0092] c: Then charge at 4C, 3.5C, 3.0C, 2.75C, 2.5C, 2.25C, 2.0C, 1.75C, 1.5C, 1.25C, 1C, 0.75C, 0.5C, 0.33C; monitor and set the negative electrode-reference auxiliary potential 0V jump (i.e., for example, a 4C charge, when the negative electrode-reference auxiliary potential reaches 0V, a jump occurs, and then charging starts at 3.5C). Record the time when the battery is charged to 80% SOC as T1, T1-T0 is the fast charge time, in min. Test temperature 25±2℃.

[0093] 3. Energy density test.

[0094] The test method is as follows:

[0095] a: Charge the battery at a constant current of 0.33C to an upper voltage of 4.25V, then charge at a constant voltage until the cut-off current is less than or equal to 0.05C, and then discharge;

[0096] Repeat the above steps 3 times, and take the third discharge energy as the discharge energy E of the battery;

[0097] b: The battery weight M is obtained by weighing with an electronic balance;

[0098] c: Calculation of weight energy density: E / M, unit: Wh / Kg.

[0099] The fast charging time and energy density data of the batteries under the conditions of various embodiments and comparative examples are shown in Table 2 below.

[0100] Table 2

[0101]

[0102]

[0103] From the data results in Table 1 and Table 2, it can be seen that by comprehensively controlling b, d and m, While ensuring a relatively high energy density, the battery's fast charging performance can also be guaranteed. In particular, by further optimizing When the value of is in the range of -1.8 to -0.7, a battery with higher energy density and better faster charging performance can be obtained. Specifically, for the solution in which the long side length L of the above-mentioned negative electrode sheet is 450mm, the fast charging time is ≤45min, preferably ≤20min; the energy density is ≥250WH / KG, preferably ≥270WH / KG, and more preferably ≥290WH / KG. For the solution in which the long side length L of the above-mentioned negative electrode sheet is 1000-1100mm, the fast charging time is ≤50min, preferably ≤30min; the energy density is ≥300WH / KG, preferably ≥310WH / KG.

[0104] Obviously, the above embodiments are only examples for clear explanation, and are not intended to limit the implementation methods. For ordinary technicians in the relevant field, other different forms of changes or modifications can be made based on the above description. It is not necessary and impossible to list all the implementation methods here. The obvious changes or modifications derived from them are still within the protection scope of the invention.

Claims

1. A battery, comprising a battery cell, wherein the battery cell comprises a negative electrode sheet and a tab disposed on the negative electrode sheet; characterized in that: The negative electrode active material layer of the negative electrode sheet contains silicon, and the mass percentage of silicon in the negative electrode active material layer is b, in %; parallel to the long side direction of the negative electrode sheet, the longest distance between the pole ear and the end of the negative electrode sheet is d, in mm; the lead-out direction of the pole ear is the first direction, and perpendicular to the first direction, the dimension of the connection between the pole ear and the negative electrode sheet is the width of the pole ear m, in mm; b, d and m satisfy the following relationship:

2. The battery according to claim 1, characterized in that The value is -1.8 to -0.

7.

3. The battery according to claim 1 or 2, characterized in that: The value of b is 1.25 to 16; And / or, the value of d is 42 to 1000; And / or, the value of m is 9-960.

4. The battery according to claim 3, characterized in that The value of b is 2.5 to 10; And / or, the value of d is 250 to 450; And / or, the value of m is 50-180.

5. The battery according to claim 1 or 2, characterized in that: The surface density of the negative electrode active material layer is 90 to 300 g / m 2 .

6. The battery according to claim 1 or 2, characterized in that: The compaction density of the negative electrode active material layer is in the range of 1.2 to 2.3 g / cm 3 .

7. The battery according to claim 1 or 2, characterized in that: The tab is extended from the long side of the negative electrode sheet, and the ratio of the tab width to the negative electrode sheet width is greater than or equal to 0.5 and less than or equal to 1 perpendicular to the tab extension direction. And / or, the long side length L of the negative electrode sheet is ≥ 300 mm; And / or, the battery cell is a laminated battery cell.

8. The battery according to claim 1 or 2, characterized in that: The positive electrode sheet included in the battery cell uses a positive electrode active material of LiNi x Co y Mn z O2 material, wherein 1>x≥0.5, x+y+z=1.

9. An electrochemical device, characterized in that: A battery comprising any one of claims 1 to 8.

10. An electrical device, characterized in that: An electrochemical device comprising the electrochemical device according to claim 9.

Citation Information

Patent Citations

  • Electrochemical device and electronic device including same

    CN111525194A

  • Laminated battery

    JP2010232146A

Cited By

  • Negative pole piece, battery, energy storage device and electric equipment

    CN120878741A

  • Battery, electrochemical apparatus, and electrical apparatus

    WO2026123583A1